Реалізація конституційного права на працю особами з обмеженими можливостями - Filipska, N. O.; Філіпська, Н. О.; ORCID: http://orcid.org/0000-0002-9558-9422 (Конституційно-правові академічні студії. – 2018. – № 2. – С. 70-78, 2018)
Стаття присвячена дослідженню питань реалізації в Україні особами з обмеженими можливостями права на працю, гарантованого Конституцією та міжнародними документами. Розглянуто низку законодавчих актів України,що регулюють питання праці та зайнятості, в тому числі й осіб з обмеженими можливостями. Висловлено думку щодо доцільності створення умов та надання змоги особам, яких визнано «непрацездатними», займатися (за їх бажанням) таким видом трудової діяльності, яка відповідає їхнім індивідуальним можливостям. Дієвим механізмом реалізації права зазначених осіб на працю автор вважає впровадження системи підтриманої зайнятості для даної категорії осіб. У результаті аналізу даних зроблено висновок, що впровадження та функціонування системи підтриманої зайнятості позитивно впливає на ситуацію з працевлаштуванням та зайнятістю серед осіб з обмеженими можливостями. The article is focused on the issues of implementing the right to labor by the persons with disabilities in Ukraine, which is guaranteed by the Constitution and international documents. The author has studied a number of legislative acts of Ukraine regulating labor and employment issues, including those that concem the people with persistent health complications (director disability), and especially of psycho-intellectual and complex nature, is quite acute in Ukraine. The positive innovation experience of some public organizations that people jobs for people with disabilities, mostly with psycho-intellectual disabilities, is worth to have government support. The author considers the effective mechanism of the realization of the right to labor for these persons. There is an opinion that the notion of “labor” in this context (as an activity that is not necessarily paid)are not identical. As a result of data analysis, it has been concluded that the implementation and functioning of the supported employment system positively affects the situation with placement and employment among people with disabilities. The author has offered a number of measures that can facilitate effective actions to maximize the involvement of person of this category to labor and employment.
Філіпська Н.О. Реалізація конституційного права на працю особами з обмеженими можливостями / Філіпська Н.О. // Конституційно-правові академічні студії. – 2018. – № 2. – С. 70-78.
Keywords: особи з обмеженими можливостями; праця та зайнятість; підтримана зайнятість; конституційне право на труд; громадські утворення; соціалізація; інклюзія; persons with disability; labor and employment; supported employment; constitutional labor right; human society; socialization; inclusion